Organizational Culture Automated Audit System (OCAAS) - Al - Jubair, Md. Abdullah (unimas, 2017)
Organizational culture is a system of collective assumptions, morals, and views, which governs how people act in organizations. An organizational culture audit (OCA) is a complete investigation and assessment of an organization’s culture. There are several studies that have been done on OCA but mainly based on manual cultural audit. The study discovered some drawbacks of manual OCA of which are: accuracy, time consuming, and cost. Review of literature implicated that there is no standard procedure to follow or any system methodology that has been developed this far. The study suggests the development of data mining based on knowledge management technology that can be utilized in automated OCA to overcome the many drawbacks. A new framework was proposed for automated OCA and development of the OCA system named as Organizational Culture Automated Audit System (OCAAS). Several state of the art technologies and techniques were used to design and developed OCAAS which include the use of machine learning and sentiment analysis based novel opinion mining algorithms for electronic opinion analysis and computerized statistics based mathematical algorithms for electronic data analysis as well as MySQL database integration for faster data processing and cognitive ergonomics system interface for user friendly interface navigation.